Translation Studies – The State of the Art - Wilss, Wolfram (Meta, 2004)
AbstractTranslation has spoken with growing impact and urgency to mankind for more than two millennia. Not only has it facilitated the understanding of sociocultural structures, economico-political systems, and technological/technical processes; it has also pushed forward our knowledge of the world (including our awareness of “otherness”) and widened our (inter-) linguistic and (inter-)cultural horizon.